(untitled) (European Journal of Pure and Applied Mathematics, 2024)
Our main purpose is to introduce the concepts of upper and lower α-⋆-continuous multifunctions. In particular, some characterizations of upper and lower α-⋆-continuous multifunctions are investigated.